Effect of a Synthetic Thrombin Inhibitor MCI-9038 on Experimental Models of Disseminated Intravascular Coagulation in Rabbits - Hara, H; Tamao, Y; Kikumoto, R; Okamoto, S (Thrombosis and Haemostasis, 1987)
We examined the effect of a synthetic thrombin inhibitor, MCI-9038, on two experimental animal models of disseminated intravascular coagulation (DIC).In a model that DIC induced by the intravenous infusion of thrombin, MCI-9038 suppressed the decrease of platelet count by about 50% at a dose of 0.2 μg/kg/min and almost completely at 2 μg/kg/min. When MCI-9038 was administered orally, the suppressive effect was also observed. Heparin suppressed the platelet count decrease by about 50% at 1 unit/kg/min.In another model of DIC induced by lactic acid and tissue thromboplastin infusion, MCI-9038 prevented the decrease of platelet count and the consumption of coagulation factors. The suppression effect by about 50% on these changes was observed at a dose of 3.16 μg/kg/min. Thromboelastogram pattern indicating the consumption coagulopathy in control experiments was normalized by the MCI-9038 administration. Heparin suppressed the decrease of fibrinogen content as effectively as MCI-9038, but it was less effective on the platelet count decrease.From these results, it was concluded that MCI-9038 might be useful for the treatment of DIC.
Keywords: Thrombin inhibitor; MCI-9038; DIC; Heparin